Clinical and Biochemical Evaluation of Atypically Presented Childhood Nephrotic Syndrome - Mahmud, Nasir Uddin; Sharma, Jhulan Das; Azad, Abul Kalam; Barua, Chowdhury Chimnjib; Kamal, Abu Hena Mostafa (Journal of Chittagong Medical College Teachers’ Association, 2011)
Key words: nephrotic syndrome; proteinuria; oedema DOI: 10.3329/jcmcta.v21i1.7680 Journal of Chittagong Medical College Teachers' Association 2010: 21(1):56-61